ON FEATURED IOT FOR SMART PUBLIC TRANSPORTATION WITH CLOUD-BASED MACHINE LEARNING - Mochamad Nizar Palefi Ma'ady (NJCA (Nusantara Journal of Computers and Its Applications), 2018)
With rapid development of science and technology and the accelerated pace of urbanization, smart city has been also widely spread across our country. By Internet of Things, we put forward a kind innovative way of real-time air pollution monitoring into public city transportation vehicle. We take information about the surrounding environment through sensors and upload it directly to the internet. This paper fosters the advantages of the cloud-based computing frameworks (such as Microsoft Azure Machine Learning Studio) and presents a practical work-flow well-suited for the standard machine learning tasks.